The rights of women and children as internally displaced persons : the case of Uganda and the Democratic Republic of Congo (DRC) - Boukongu, Jean-Didier (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.